Milk Production and Quality of Murrah Buffalo Supplemented by Turmeric Powder and Casava Leaf in Agam Regency, Indonesia - Roza, Elly; Susanty, Hilda; Aritonang, Salam N.; Sriwahyuni, Putri; Hendri, Jhon; Rizqan (Journal of Buffalo Science, 2024)
Buffalo farming in Indonesia is still managed traditionally due to low milk production and quality. Like in other developing countries, buffalo farming has becomea side business. Murrah Buffalo milk has better fat and protein content compared to dairy milk. Production and quality of buffalo milk affect farming management, such as keeping systems and feed management. The study aimed to reveal the effect of turmeric powder supplement and cassava leaf as forage on Murrah Buffalo in terms of milk production and quality (protein, fat, and lactose content). The study was conducted experimentally for four female Murrah Buffalo fed several formula feeds. The formula feed treatments are A (basal feed 100%), B = A + cassava leaf (1kg) + Turmeric Powder (0.015% Body weight), C = A + Cassava Leaf (1.5kg) + Turmeric Powder (0.030% Body Weight), D = A + Cassava Leaf (2kg) + Turmeric Powder (0.045% Body Weight). The result shows Milk production, protein, fat, and lactose is 5.40-7.91kg, 2.93-3.41%, 4.81-10.69%, and 4.39-5.11%, respectively. In summary, the best turmeric powder supplementation and Cassava leaf supply belong to treatment D, which significantly increases Murrah Buffalo milk production and quality.